Death Becomes Her: Capitalism in Crisis and Imperialism - Corrêa, Hugo (2021)
In the article we present an interpretation of the relationship between crises, imperialism, and social critique connecting two distinct historical periods: the period of formulation of the classical theory of imperialism and the current period. Our objective was to understand how Marxism responded to the crisis that led to World War I and how this response could serve to face our current impasses. We emphasize that the Covid-19 pandemic, the climate emergency, and imperialist tensions are intertwined dimensions of the contemporary crisis of capital, whose parallel with the historical process experienced by Marxism at the beginning of the last century must be found in the imminence of barbarism and the need for radical criticism.